Multipoint focal boundary value problems on infinite intervals. (1992) - Umamaheswaram, S.; Rama, M. Venkata
Abstract : For the differential equation y ( n ) = f ( x, y ), we state a set of necessary and sufficient conditions for the existence of a solution (i) on a semi-infinite interval for a k -point right focal boundary value problem and (ii) on ( − ∞, ∞ ) for a ( n − 1 ) -point right focal boundary value problem. The conditions are in terms of the existence of a pair of solutions u ( x ), v ( x ) satisfying some auxiliary boundary conditions and algebraic inequatilities.